Comparative study on design for prestressed concrete in different countries with computer programming - Saeed, Imran; Ueda, Tamon; Pama, Ricardo P.; Wireland, Martin; The Royal Norwegian Government, NORAD (Bangkok : Asian Institute of Technology, 1988)
A computer program has been developed for the design of simply sup ported prestressed concrete members . This program can accommodate the provisions of the design codes suggested by the American Concrete Insti tute, British Standards Institute and the Japanese Society of Civil En gineers. The results obtained by following these codes are compared. Special emphasis is given to the design of members in shear. A correlation is developed between the provisions suggested by the three codes for the shear taken by a section without shear reinforcement. A comparison of the economy of the design in shear of the three codes is made . Other aspects like flexural strength, fatigue, deflection and cracking are also discussed
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Prestressed concrete -- Data processing